RESEARCH APPROACHES TO THE DEVELOPMENT OF THE PROBLEM OF CORRUPTION AND BRIBERY IN THE UKRAINIAN PROVINCES IN THE SECOND HALF OF THE 19TH - AT THE BEGINNING OF THE 20TH CENTURY - Бурилов, Костянтин (SWorldJournal, 2024)
The article highlights and analyzes the scientific works of scientists who studied the peculiarities of the credit and banking system, law enforcement agencies and the administrative and bureaucratic apparatus of the Ukrainian provinces of the Russian Emp